#### Answer

$\frac{27}{92}$

#### Work Step by Step

We are given that $a=-3$, $b=64$, and $c=6$.
Therefore, $\frac{3c+a^{2}}{2b-6c}=\frac{3(6)+(-3)^{2}}{2(64)-6(6)}=\frac{18+9}{128-36}=\frac{27}{92}$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$\frac{27}{92}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.